Exercise and Motor Training in People with Parkinson's Disease: A Systematic Review of Participant Characteristics, Intervention Delivery, Retention Rates, Adherence, and Adverse Events in Clinical Trials - Natalie E. Allen; Catherine Sherrington; Gayanthi D. Suriyarachchi; Serene S. Paul; Jooeun Song; Colleen G. Canning (Parkinson's Disease)
There is research evidence that exercise and motor training are beneficial for people with Parkinson's disease (PD), and clinicians seek to implement optimal programs. This paper summarizes important factors about the nature and reporting of randomized controlled trials of exercise and/or motor training for people with PD which are likely to influence the translation of research into clinical practice. Searches identified 53 relevant trials with 90 interventions conducted for an average duration of 8.3 (SD 4.2) weeks. Most interventions were fully supervised (74%) and conducted at a facility (79%). Retention rates were high with 69% of interventions retaining ≥85% of their participants; however adherence was infrequently reported, and 72% of trials did not report adverse events. Overall, the labor-intensive nature of most interventions tested in these trials and the sparse reporting of adherence and adverse events are likely to pose difficulties for therapists attempting to balance benefits and costs when selecting protocols that translate to sustainable clinical practice for people with PD.